2015
DOI: 10.1039/c5tc01699a
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronic properties and color chemistry of native point defects in Al:ZnO transparent conductive oxide

Abstract: We present a first principles study on the effect of native point defects in Al:ZnO transparent conductive oxide. Our results indicate that oxygen and zinc vacancies play two completely different roles:the former maintain the electrical properties while worsening the transparency of native Al:ZnO. The latter are strong electron acceptors that can destroy the metal-like conductivity of the system. While the percentage of doping amount is not really relevant, the compensation ratio between Zn vacancies and Al do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…All defective ZnO structures were fully relaxed to the minimum energy configurations. Electronic structures of the resulting systems well agree with previous calculations [ 18 , 19 , 20 ]: undefective ZnO has a semiconducting behavior with the Fermi level lying in the middle of the bandgap (E = 3.2 eV). V is a deep defect, which introduces fully occupied states in the bandgap.…”
Section: Resultssupporting
confidence: 85%
“…All defective ZnO structures were fully relaxed to the minimum energy configurations. Electronic structures of the resulting systems well agree with previous calculations [ 18 , 19 , 20 ]: undefective ZnO has a semiconducting behavior with the Fermi level lying in the middle of the bandgap (E = 3.2 eV). V is a deep defect, which introduces fully occupied states in the bandgap.…”
Section: Resultssupporting
confidence: 85%
“…As explicitly demonstrated for the similar case of Al-doped ZnO 32 , ω p is not an intrinsic property of the material, as it happens for noble metals, but can be properly engineered by controlling the electron density, i.e. by changing the doping and defect concentration 33 . The tunability of the plasma frequency has important implications from the application viewpoint, since it allows to engineer the operating frequency region of the material in connection with other dielectric layers for realization of metamaterials and surface plasmon polariton (SPP) waveguides.…”
Section: Resultsmentioning
confidence: 97%
“…This is an efficient and computationally inexpensive way to correct for the severe underestimation of the band gap and the wrong energy position of the d -bands of the Zn atoms 47 , 48 , 51 , 52 . On the other hand U values for the dopant species, namely Al and Cu, as immersed in the host matrix, are negligible 53 . The adopted U values for both elements have been calculated using the pseudo-hybrid implementation of DFT + U (ACBN0) 47 , 48 .…”
Section: Methodsmentioning
confidence: 98%
“…Wang et al [29] prepared pristine ZnO films, and found that the introduction of the green luminescence is correlated with the formation of the Zn vacancy-related defect (V Zn ). Theoretical studies of the effect of vacancy defects in metal element-doped ZnO were performed in [31][32][33][34][35][36]. Bai et al [31] studied the electronic and optical properties of 2D ZnO:Mg/Be with V O or V Zn .…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that V O will cause a blue-shift, whereas V Zn will cause a red-shift in the optical absorption spectra. Alessandra et al [32] presented a first-principles study on the effect of native point defects in Al:ZnO transparent conductive oxide. They found that V O defects maintain the electrical properties but worsen the transparency of native Al:ZnO, whereas V Zn defects are strong electron acceptors that can destroy the metal-like conductivity of the system.…”
Section: Introductionmentioning
confidence: 99%